PENERAPAN NILAI-NILAI AQIDAH DALAM KEGIATAN EKSTRAKURIKULER HADRAH DI MTs KP KARANGJATI NGAWI - Dian Febrianingsih (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2020)
This study aims to determine: 1) The process of extracurricular hadrah activities at MTs KP Karangjati Ngawi 2) The values ​​of aqidah that are applied in extracurricular hadrah activities at MTs KP Karangjati Ngawi. This type of research is a case study in field research (field research). The technique of determining the research subject uses non-probability sampling with purposive sampling, which determines the sample with certain considerations and goals. In this study, the research subjects were teachers of hadrah extracurricular activities, students participating in extracurricular hadrah activities and community users of the hadrah team at MTs KP Karangjati Ngawi. Based on the results of data analysis, the research results obtained are: 1) the process of extracurricular activities at MTs KP Karangjati Ngawi is carried out every Friday from 13.00 - 16.00 and has full support from the head and teachers of MTs KP Karangjati Ngawi, 2) values aqidah contained in extracurricular hadrah activities at MTs KP Karangjati is an implementation of the pillars of faith which are summarized in the competence of faith, namely: feeling the supervision of Allah Almighty in all actions; pray diligently; thankful diligently; learn to be patient; learn piety and try to avoid immorality.